Pemanfaatan Limbah Cangkang Kerang Kepah (Polymesoda Erosa ) Sebagai Katalisator Pada Proses Carburizing - Yuhardin, Yuhardin; Ramli, Ramli; Sugiyarto, Sugiyarto (Jurnal Inovasi Teknologi Terapan, 2024)
In general, the shells are widely used as handicraft materials such as wall decorations or building interior decorations and as a mixture of animal feed, therefore other utilization is needed to increase the use value of the shells. Clam shells contain calcium in the form of calcium carbonate (CaCO3) by 96.5%. The high calcium content of the shell allows the shell to be used as a source of catalyst material in the carburizing process. The catalyst affects the carburizing process because it can accelerate the formation of CO2 gas, which is needed for the carbon diffusion process on the surface of low carbon steel so that the metal hardness can increase. The powder mixing process was carried out for 3, 6, 9 hours with the variations used, namely 0%, 10%, 20%, 30% to determine the effect of the percentage of mussel shell powder catalyst and carburizing process time on the hardness value and impact strength of ST 42 steel.